Rapid intraoperative amplicon sequencing of CNS tumor markers - Maximilian Evers; Björn Brändl; Christian Rohrandt; Carolin Kubelt-Kwamin; Franz-Josef Müller; Dominik Danso; André Maicher; Gaojianyong Wang; Sönke Friedrichsen; Stephan Kolkenbrock (Computational and Structural Biotechnology Journal)
Currently, central nervous system tumors are diagnosed with an integrated diagnostic approach that combines histopathological examination with molecular genetic profiling, which requires days to weeks to achieve a precise and informative classification of CNS tumors. This study demonstrates the feasibility of rapid multiplex amplicon nanopore sequencing for identifying critical mutations relevant to molecular stratification of brain tumors within the timeframe of standard resection surgery. Utilizing live analysis of nanopore sequencing data, we evaluated the brain tumor-associated molecular markers IDH1 R132, IDH2 R172, pTERT C228 and C250, H3F3A K27 and G34, Hist1H3B K27, and BRAF V600. Our method achieved a turnaround time of 105 min at the point-of-care from receipt of a tumor biopsy to result with the potential to impact surgical strategy. Our approach can be integrated with recently developed DNA methylation-based diagnostic classification systems, corroborating diagnoses and even further specifying tumor grades, thus enabling a multimodal diagnostic intraoperative assessment of CNS malignancies.